A new species and new record of the genus Platybaetis Müller-Liebenau, 1980 (Ephemeroptera: Baetidae) from Eastern Himalaya, India - Kubendran, T.; Vasanth, M.; Subramanian, K. A.; Jabeen, Fatima; Sivaramakrishnan, K. G.; Mitra, Pallabi (Zootaxa, 2021)
A new species of Platybaetis viz., P. selvai sp. nov. is described herein based on larval collections from Tangon stream in the state of Arunachal Pradesh in Eastern region of Indian Himalaya. It can be differentiated by the following combination of characters: (i) posterior margin of abdominal segments I–X with rounded ‘U’ shaped spines; (ii) anterolateral margin of gills I–VII with minute setae; (iii) claw with 7–8 denticles; (iv) paracercus composed of 10–11 segments; (v) hindwing pads reduced, small. Brief ecological notes are appended.